HIV-induced T-cell activation/exhaustion in rectal mucosa is controlled only partially by antiretroviral treatment (2012)
ABSTRACT: Peripheral blood T-cells from untreated HIV-1-infected patients exhibit reduced immune responses, usually associated with a hyperactivated/exhausted phenotype compared to HAART treated patients. However, it is not clear whether HAART ameliorates this altered phenotype of T-cells in the gastrointestinal-associated lymphoid tissue (GALT), the main site for viral replication. Here, we compared T-cells from peripheral blood and GALT of two groups of chronically HIV-1 infected patients: untreated patients with active viral replication, and patients on suppressive HAART. We characterized the T-cell phenotype by measuring PD-1, CTLA-4, HLA-DR, CD25, Foxp3 and granzyme A expression by flow cytometry; mRNA expression of T bet, GATA-3, ROR-ct and Foxp3, and was also evaluated in peripheral blood mononuclear cells and rectal lymphoid cells. In HIV-1+ patients, the frequency of PD-1+ and CTLA-4+ T-cells (both CD4+ and CD8+ T cells) was higher in the GALT than in the blood. The expression of PD-1 by T-cells from GALT was higher in HIV-1-infected subjects with active viral replication compared to controls. Moreover, the expression per cell of PD-1 and CTLA-4 in CD4+ T-cells from blood and GALT was positively correlated with viral load. HAART treatment decreased the expression of CTLA-4 in CD8+ T cells from blood and GALT to levels similar as those observed in controls. Frequency of Granzyme A+ CD8+ T-cells in both tissues was low in the untreated group, compared to controls and HAART-treated patients. Finally, a switch towards Treg polarization was found in untreated patients, in both tissues. Together, these findings suggest that chronic HIV-1 infection results in an activated/exhausted T-cell phenotype, despite T-cell polarization towards a regulatory profile; these alterations are more pronounced in the GALT compared to peripheral blood, and are only partiality modulated by HAART